Calculation of the Cross-Section and Neutron Yield for Production Reactions of Gallium-67 - Tawfeek, Huda Majeed; Amin, Amin Kadhum; Mahdi, Khalid Hadi (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The study of cross-section and the neutron Yield of Gallium–67 isotope is a very necessary choice in the field of nuclear medicine, which is used in radiopharmaceuticals and for medical diagnosis and treatments. The cross-section of 68Zn (p,2n) 67Ga, 67Zn (p, n) 67Ga was calculated for different energies by using different sets of programs using MATLAB language. The cross-section was then used to calculate the neutron yields. The results of the neutron yield distributions have been used to generate polynomial expressions with incident proton energies. We also calculated the stopping power through the Ziegler formula using the computer program   (SRIM 2013) to calculate the two reactions mentioned above and also compared the results for stopping powers for the above reactions with the computer program (MATLAB 2017). Then, the neutron yield was calculated for these two reactions to find the best reaction with the highest neutron Yield in our study and use it to calculate the isotope production Yield for these reactions and other results within this study.